Learning from Disaster Response and Public Health Emergencies : The Cases of Bangladesh, Bhutan, Nepal, and Pakistan - Mohammed-Roberts, Rianna; Ajumobi, Oluwayemisi Busola; Guzman, Armando (World Bank, Washington, DC, 2021)
This study analyzes responses to past natural disasters in four countries in South Asia - Bangladesh, Bhutan, Nepal, and Pakistan. Of 178 hazardous events reported in the four countries during the 10 years covered by this study (2009-19), 126 were classified as disasters and used for the in-depth analysis. The analysis revealed that countries have multi-hazard preparedness and response capacities in place, albeit to varying degrees, in areas such as early warning and surveillance systems, emergency operations centers, and whole-of-society approaches to disaster preparedness, response, and recovery. Notwithstanding, the analysis also revealed gaps across each country in their capacity to detect, prepare for, respond to, and recover from hazard-induced disasters, including public health emergencies. To address these gaps, the paper offers recommendations for improving capacities and resilience to disasters. Recent infectious disease outbreaks, including the ongoing global Coronavirus 2019 (COVID-19) pandemic, have demonstrated the critical importance of comprehensive disaster risk management systems, which include resilient health systems, in reducing exposure and vulnerabilities to hazards, with an overarching aim of safeguarding national and global health security. To ensure sustainability, this calls for, amongst others, a holistic approach to resilience that incorporates public health, disaster risk, and climate change considerations; the integration of community-based disaster risk reduction programs into routine public health service delivery functions; an enhanced and expanded focus on improving multi-hazard preparedness; and the prioritization and institutionalization of after action reviews, as a means of ensuring that corrective actions from past public health events are properly considered.